النظام القانوني لناظر الوقف (دراسة مقارنة) - - .نصيرة بدبودي. (Universté ELOUEd-جامعة الوادي, 2020)
يهدف هذا البحث الى دراسة واقع النظارة على أموال الوقف والمركز القانوني للناظر في التشريع الجزائري مقارنة مع نظيره في القانون الكويتي، للوصول إلى مقترحات من النصوص التشريعية والتنظيمية من اجل تطوير المنظومة المؤسسية لإدارة الوقف، وتحسين كفاءة القائمين عليها، ولنشر ثقافة الاهتمام بالوقف وكيفية إدارة أمواله وتوظيفها في تمويل المشاريع الاستثمارية وعصرنتها ولتحسين مخرجاتها. حيث اعتمدت في هذا البحث على المنهج الوصفي، مبينة من خلاله ماهية النظارة والناظر في صورتيه الطبيعي والاعتباري، كما وضحت مشروعية النظارة وطبيعتها واقسامها واركانها طبقا لإحكام الفقه الإسلامي، واعتمدت ايضا المنهج المقارن والاستقرائي فتم سرد المواد القانونية، واجراء موازنة بينها في كلا التشريعين. وفي الأخير توصلت الدراسة إلى مجموعة من الإجراءات المقترحة منها اعادة النظر في قانون الاوقاف الجزائري بإضافة بعض النصوص التشريعية والتنظيمية، وإنشاء هيئة إدارية متخصصة لنظارة الأوقاف مستقلة النظام المركزي للوزارة.This research aims at dramatizing the reality of the overseer on endowment funds and the legal position of the observer in Algerian legislation compared to its counterpart in Kuwaiti law. The current study intends to reach proposals from legislative and regulatory texts for the development of the institutional system of Waqf administration، improving the efficiency of those in charge of it، spreading the culture of endowment interest and how to manage its funds، and using them in financing and modernizing investment projects to improve their outputs. In doing so، the descriptive and the comparative approaches are conducted. Firstly، the descriptive method is used to show the nature of the endowment overseer in his natural and legal images، as well as the legality of the observers and their nature، divisions and pillars in accordance with the provisions of Islamic jurisprudence. Secondly، the comparative and inductive approaches are adopted to list the legal articles and to make a balance between them in both legislations. This study reached a set of proposed measures including reviewing the Algerian endowment law by adding some legislative and regulatory texts. Moreover، establishing a specialized administrative body to observe the endowments which are independent from the central system of the ministry.
مذكرة ماستر
Keywords: النظارة - أموال الوقف -الأوقاف; independent from -dramatizing the reality of the overseer